2007
DOI: 10.1038/sj.cgt.7701075
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular events associated with the antitumor response induced by the cytosine deaminase/5-fluorocytosine suicide gene therapy system in a rat liver metastasis model

Abstract: The bacterial cytosine deaminase (CD) gene converts the non-toxic prodrug 5-fluorocytosine (5-FC) into 5-fluorouracil. We have previously shown, in a rat liver metastasis model from colon carcinoma, that intratumoral injection of a CD-expressing plasmid into the animals followed by 5-FC treatment results in the regression of the treated tumor as well as distant uninjected tumors. The aim of this study was to further analyze the mechanisms associated with tumor regression induced upon application of suicide CD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The use of an immunocompetent murine model, such as that used in the present work, offers the possibility of studying the contribution of NK and CD8-T cells and immunomodulators to the tumor regression induced by the suicide gene therapy. [52][53][54][55] In this context, our results show that delivery of the suicide genes mediated by Tf-lipoplexes results in an increase of tumoral infiltration of NK and T cells, mainly cytotoxic CD8-T cells, in the treated animals when compared with controls ( Figure 5). This increase may be partly responsible for the observed antitumoral activity.…”
Section: Discussionmentioning
confidence: 88%
“…The use of an immunocompetent murine model, such as that used in the present work, offers the possibility of studying the contribution of NK and CD8-T cells and immunomodulators to the tumor regression induced by the suicide gene therapy. [52][53][54][55] In this context, our results show that delivery of the suicide genes mediated by Tf-lipoplexes results in an increase of tumoral infiltration of NK and T cells, mainly cytotoxic CD8-T cells, in the treated animals when compared with controls ( Figure 5). This increase may be partly responsible for the observed antitumoral activity.…”
Section: Discussionmentioning
confidence: 88%
“…18). Recent studies confirmed that a reduction or depletion of hepatic NK cells could enhance tumor growth in the liver (19), whereas enhanced NK activity contributed to reduced liver metastases in several tumor models (20,21). Moreover, indirect evidence suggests that susceptibility of human cancer cells to NK-mediated immune attack can affect their ability to generate liver metastases (22).…”
Section: Cells Of the Hepatic Sinusoid Can Kill Tumor Cellsmentioning
confidence: 90%
“…25,36 Unlike mammalian thymidine kinase, HSV-TK can phosphorylate ganciclovir and the monophosphate form of ganciclovir is subsequently phosphorylated by endogenous cellular kinases to the triphosphate form, which inhibits DNA polymerase and, The radiosensitization effect of the CD/5-FC combination may be due to the accumulation of cells in early S phase and a consequent increase in DNA strand breakage. 25,36 In contrast, the radiosensitization effect of the HSV-TK/ganciclovir combination is probably due to inhibition of the repair of potentially lethal damage. 26 Thus, following double prodrug treatment, CD-TK-expressing cells suffer increased DNA strand breakage after ionizing radiation (due to the CD/5-FC system) and concomitantly are unable to replicate and repair DNA (due to the HSV-TK/ganciclovir system).…”
Section: Discussionmentioning
confidence: 99%